Synthesis and characterization of carbon coated nanograined lithium iron phosphate (LiFePO4) as cathode material for lithium-ion batteries - Llanos, Princess Stephanie P. (College of Engineering, University of the Philippines Diliman, 2015)
The depleting supply and harmful effect to the environment of fossil fuel as power source have forced the development of renewable energy and energy storage systems. Electrochemical devices such as batteries store energy and store it as electricity by converting chemical into electrical energy. Lithium-ion batteries have been considered to be one of the top performing electrical energy storage units. Lithium iron phosphate (LiFePO4) is a potential cathode material for lithium-ion batteries due to its promising characteristics such as high theoretical capacity (170 mAhg-1), high cycling performance, moderate operating voltage (3.45V vs Li+/Li), high thermal stability, low cost, and low toxicity. However, the challenges for this material are its poor electronic conductivity and low lithium-ion diffusion coefficient. In this study, carbon-coated nanograined LiFePO4 is synthesized via wet chemistry method at a low temperature of 400ºC and is investigated for its performance as a cathode in lithium-ion battery. The synthesized LiFePO4 are fully characterized for its thermal, structural, morphological, and electrochemical properties. The precursor of LiFePO4 revealed three distinct stages of weight loss from the thermogravimetric analysis. The observed peaks from X-ray diffraction pattern of the synthesized samples were indexed to the orthorhombic LiFePO4 with (311) as the dominant peak. The cell parameters reported are close to the theoretical values and the calculated average grain sizes are in nanometer range (30-230 nm). The FTIR spectra reported matched that of a commercial LiFePO4. Agglomerated particles that range from 200nm to 300nm are reported by scanning electron microscopy. TEM images confirmed the crystallinity structure of LiFePO4 and coating of amorphous carbon layer. EDS showed the presence and homogeneous dispersion of Fe, P, O, and C elements. Furthermore, the electrode performance of the synthesized cathodes were investigated using cyclic voltammetry, capacity measurements using Galvanostatic charge/discharge tests, C-rates and cycling performance. Galvanostatic charge and discharge measurements indicated that the sample sintered at 400ºC for 3 hours with excess carbon demonstrated the highest capacity among the samples which is 160 mAhg-1 at 0.1C rate, higher than the commercial LiFePO4. Hence, in this study, the observed good electrochemical properties of the synthesized sample can be ascribed to its nanostructured particles and successful incorporation of carbon